Do Topical Corticosteroids Induce Histologic Remission and Improve Clinical Symptoms in Eosinophilic Esophagitis? - : A Systematic Review and Meta-Analysis - Ghazaleh, Sami (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.